2007
DOI: 10.1519/r-18795.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hamstring-Emphasized Resistance Training on Hamstring:Quadriceps Strength Ratios

Abstract: A decreased hamstring:quadriceps (H:Q) ratio may put the hamstrings and anterior cruciate ligament (ACL) at increased risk of injury. Therefore, the purpose of this study was to evaluate H:Q ratios of 12 female National Collegiate Athletic Association soccer players, and to test the effects of a 6-week strength training program on these ratios. Each subject completed 2 practice sessions before a pretest. Subjects then completed 6 weeks of strength training that included the addition of 2 hamstring specific exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 0 publications
10
122
1
9
Order By: Relevance
“…For muscular capacity, 11 studies have looked into its association with sustaining a non-contact ACL injury (Ahmad, et al, 2006;Bee-Oh, et al, 2009;Bowerman, Smith, Carlson, & King, 2006;Grygorowicz, Kubacki, Pilis, Gieremek, & Rzepka, 2010;Hiemstra, Webber, MacDonald, & Kriellaars, 2007;Holcomb, Rubley, Lee, & Guadagnoli, 2007;Hosokawa, et al, 2011;Mattacola, et al, 2002;Roberts, Ageberg, Andersson, & Fridén, 2007;Wilkerson, et al, 2004;. These studies have associated muscular capacity with risks of acquiring ACL injury, validating ACL screening tools to be used in intervention programs to prevent ACL injury.…”
Section: Reflection On Associative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For muscular capacity, 11 studies have looked into its association with sustaining a non-contact ACL injury (Ahmad, et al, 2006;Bee-Oh, et al, 2009;Bowerman, Smith, Carlson, & King, 2006;Grygorowicz, Kubacki, Pilis, Gieremek, & Rzepka, 2010;Hiemstra, Webber, MacDonald, & Kriellaars, 2007;Holcomb, Rubley, Lee, & Guadagnoli, 2007;Hosokawa, et al, 2011;Mattacola, et al, 2002;Roberts, Ageberg, Andersson, & Fridén, 2007;Wilkerson, et al, 2004;. These studies have associated muscular capacity with risks of acquiring ACL injury, validating ACL screening tools to be used in intervention programs to prevent ACL injury.…”
Section: Reflection On Associative Studiesmentioning
confidence: 99%
“…(Hiemstra, et al, 2007;Mattacola, et al, 2002;Roberts, et al, 2007;Wilkerson, et al, 2004; Isokinetic and isometric peak torques (Ahmad, et al, 2006;Bee-Oh, et al, 2009;Bowerman, et al, 2006;Grygorowicz, et al, 2010;Holcomb, et al, 2007;Hosokawa, et al, 2011). H:Q ratio Muscular Activation (Begalle, et al, 2012;Elias, et al, 2015;Nagano, et al, 2011;R.…”
Section: Author/yearmentioning
confidence: 99%
“…It has been suggested that females with relatively lower H/Q ratios may be at a higher risk for injury (19,20). To prevent knee injuries, an H/Q ratio of 0.6 at a minimum (the hamstrings being 60% as strong as the quadriceps) is accepted (19,21). Evidence suggests that highly developed quadriceps muscles, to a great extent, contribute to the force capacity of hamstring muscles and imbalance of the muscles (19,22).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the ways of improving H/Q ratios (23,24). It was suggested that plyometric exercises improved the ratio in physically active woman and whole body vibration training was effective on moderately active females (21,23,24). However, it is not exactly known whether aerobic exercises or spinal stability training has any impact on knee muscle strength and the H/Q ratio, and which exercise is more effective for the knee muscles in adult women.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da importância do treinamento excêntrico para a melhora da estrutura e função muscular, prevenção e reabilitação de lesões, poucos são os estudos sobre os efeitos do treinamento excên-trico nas razões de torque entre os mús-culos isquiotibiais e quadríceps (razões I:Q) [16][17][18] . A razão de torque possibilita determinar os desequilíbrios musculares entre músculos antagonistas que atuam sobre uma articulação 19,20 .…”
Section: Introductionunclassified